Training at Colorado community corrections centers: understanding and evaluating varied training approaches in the corrections environment - Dunlap, Makayla, author; Jacobi, Tobi, advisor; Doe, Sue, advisor; Gingerich, Karla, committee member (Colorado State University. Libraries, 2023)
Most depictions of the justice system suggest an environment that is strictly punitive. However, Community Corrections, as the last step before individuals reenter their community, is uniquely situated to be responsible for building agency in and actively communicating with those who have been incarcerated. This approach requires staff to be trained differently than others in the Corrections ecosystem so that they might interact with clients in a different, more humanitarian way. The current research aims to examine existing training for Community Corrections employees using the lens of Activity Theory (Engestrom, Vygotsky) and Design Justice (Costanza-Chock, Design Justice Network). To conduct this analysis, in an IRB-approved study, 24 participants, all of whom are practitioners of training or maintain some official role in the training ecosystem, were recruited from nine Community Corrections facilities across the state of Colorado and asked about their experiences with Community Corrections training. After the interviews were conducted, a critical content analysis of the qualitative data from the interviews was done, examining how the current training aligns with the six components of Activity Theory and the ten principles of Design Justice. In doing so, Activity Theory illuminates the complex and rapidly changing Community Corrections environment that staff are being trained in, while alignment with Design Justice principles helps measure the relative success of training. This project found that Community Corrections practitioners are aware of and, to some degree, are effective in applying Design Justice principles to their work even as structural challenges impede full effectiveness. However, current Design Justice principles did not fully capture the complexity of the institution. Activity Theory additionally revealed the complexity of Community Corrections organizationally and further amplified the need for structural changes that might influence overall effectiveness. This study shows that, moving forward, both Community Corrections itself and Design Justice principles can grow and improve.
Keywords: community corrections; justice system; activity theory; staff training; design justice